Porous silicon in carbon cages as high-performance lithium-ion battery anode Materials. (20th October 2017) - Zhang, Yaguang; Du, Ning; Zhu, SiJia; Chen, Yifan; Lin, Yangfan; Wu, Shali; Yang, Deren
Abstract: We demonstrate the synthesis of porous Si in carbon cages (PoSi@CC) via the oxidation of magnesium silicide, coating of carbon layer and subsequent acid washing. Different from the traditional porous Si@C core-shell(PoSi@CS) structure, new structure and morphology of PoSi@CC are obtained, and better electrochemistry performance is expressed. As the anode materials of lithium-ion batteries, the PoSi@CC particles show a capacity of 864 mAhg −1 with 91.7% capacity retention after 100 cycles at the current density of 0.4 Ag −1 . When the current density increases to 1.6 and 3.2 Ag −1, the capacity can be maintained at 590, 475 mAhg −1, respectively. The good cycling and rate performance can be attributed to the unique structures of the porous Si in carbon cages. The outer carbon layer can alleviate the pulverization and stabilize solid electrolyte interphase (SEI) film, while the enough space in the PoSi@CC particles can buffer the volume change during the charge/discharge process, which may be responsible for the enhanced electrochemical performance.